SAT0361 Kidney Involvement in Microscopic Poliangiitis – Russian Experience. (15th July 2016) - Bulanov, N.; Shchegoleva, E.; Kuznetsova, E.; Novikov, P.; Moiseev, S.
Abstract : Objectives: Our aim was to assess frequency, clinical features and prognosis of renal involvement in microscopic poliangiitis (MPA) and used treatment modalities based on experience of Clinic of Nephrology, Internal and Occupational diseases in Moscow, Russia. Methods: We performed a retrospective analysis of 61 patients with MPA, diagnosed according to Chapel-Hill Consensus Conference 2012, 23 male and 38 female, who were followed over a median of 29 (11;74) months. 58 patients (95.1% of 61) had a history of active renal vasculitis. Rapidly progressive glomerulonephritis (RPGN) was defined by the doubling of serum creatinine in ≤3 months. Acute kidney injury (AKI) and chronic kidney disease (CKD) stages were diagnosed according to KDIGO 2012 definition. Results: In 43 patients (74.1%) renal involvement developed at the onset of the disease. Other 15 (25.9%) developed glomerulonephritis after a median of 7 (6;14) months. All patients had active urinary sediment; hematuria was present in 55 (94.8% of 58) patients; 8 patients (13.8%) developed nephrotic syndrome. Nephrogenic hypertension was present in 27 (46.5%) patients. RPGN developed in 35 patients (60.3% of 58), 6 of them (17.1%) also had nephrotic syndrome. During follow up 12 patients (20.7%) developed AKI, stage 2 was diagnosed in 5 patients, stage 3 in 7 patients. In 9 patients (15.5%) AKI developed during their first admission to the hospital. Renal involvement was confirmed by kidney biopsy in 9 cases (15.3% of 59). By the end of the follow-up CKD stage 1 was diagnosed in 9 (15.5%), stage 2 in 13 (22.4%), stage 3A in 9 (15.5%), stage 3B in 12 (20.7%), stage 4 in 10 (17.3%) patients and only 5 (8.6%) developed end-stage renal disease (ESRD). Three more patients were likely to develop ESRD, but they died before it could be diagnosed according to KDIGO criteria. ESRD developed in 9 (8;13) months from the onset of the disease. A total of 4 patients (6.8%) died. As the first line induction therapy all patients received corticosteroids (CS), 51 (87.9%) – cytotoxic agents, predominantly cyclophosphamide (90.3% of 51), and 4 (6.9% of 58) – rituximab (RTX). Plasmapheresis was used in 13 (22.4%) patients. Complete remission was achieved in 40 (69%) patients who received cytotoxic agents and/or CS, 14 (24.1%) developed partial remission, in 4 (6.9%) remission was not achieved. During follow up 18 patients received RTX for remission induction due to refractory disease in 12 (66.7%), severe relapses in 2 (11.1%) and/or CS and cytotoxic agents side effects or intolerance in 8 (44.4% of 18) patients. Thirteen (72.2% of 18) patients achieved complete remission on RTX, 3 (16.7% of 18) achieved partial remission, in 2 (11.1%) RTX was ineffective. 29 patients (50%) developed one or more severe relapses during follow-up; corresponding to a relapse rate of 0.186 per patient per year. Renal relapses developed in 21 (36.2%) patients, with a renal relapse rate of 0.105 per patient per year. Conclusions: Our research revealed considerably lower prevalence of ESRD and fewer lethal outcomes in patients with MPA when compared with the published data. Nevertheless more than a half of patients develop RPGN during the course of the disease, and 46.6% have CKD stage 3B or worse by the end of the follow up. Despite effective induction therapy with high-dose CS, cytotoxic agents and/or RTX relapses, both renal and extrarenal, are frequent. Disclosure of Interest: None declared